Performance evaluation of sand dams as a rural rainwater conservation and domestic water supply technology in East-African drylands, a case-study from South-Eastern Kenya. Issue 1 (31st December 2023) - Ndekezi, Moïse; Kaluli, James W.; Home, Patrick G.
Abstract: Sand dams (SDs) are rainwater harvesting methods in East-African drylands for rural water supplies and small-scale irrigation practices. However, little information exists on their ability to maintain the harvested water in the right quantity and quality. Three SDs were selected from south-eastern Kenya's semi-arid zone as a case study to evaluate their operational performance. Water and sediment samples were collected and analyzed in both the field and laboratory. Six performance indicators, namely stormwater-capture efficiency (SCE), water-saving efficiency (WSE), volume-based and time-based reliabilities, water demand satisfaction rate (WDSR), water loss percentage, physicochemical water pollution index (WPI) and microbial non-compliance rate (NCR), were computed. Results showed that water storage in SDs is quite low and unfit for direct human consumption. In fact, three experimental SDs harvested 7, 356 m 3 during the long-rains season (March–May 2018) for an estimated water demand of 8, 990 m 3 (June–September). About 4, 505 m 3 (61.24%) was lost through evaporation (64.11%) and seepage (35.89%). These SDs exhibited low WDSR (31.72%), inadequate SCE (3.09%), low WSE (30.85%), dismal volume reliability (24.56%), and undependable time reliability (24.91%). Shallow-well water was less polluted than scoop-hole water but both didn't meet the bacterial water quality standard (0 CFU/100 mL). The former scored a low WPI of 1.86 ( reasonably clean ) compared to clean water (WPI ≤ 1), while the latter scored a high WPI of 12.91 ( considerably polluted ). Furthermore, NCRs for total coliforms were 60% in shallow wells and 90.79% in scoop holes. Therefore, this water should be treated and disinfected for domestic use.